Long‐wavelength Ultraviolet A1 and Visible Light Photoprotection: A Multimodality Assessment of Dose and Response. (30th September 2019) - Kohli, Indermeet; Braunberger, Taylor L.; Nahhas, Amanda F.; Mirza, Fatima N.; Mokhtari, Mohsen; Lyons, Alexis B.; Kollias, Nikiforos; Ruvolo, Eduardo; Lim, Henry W.; Hamzavi, Iltefat H.
Abstract: Human skin is exposed to visible light (VL; 400–700 nm) and long‐wavelength ultraviolet A1 (UVA1) radiation (370–400 nm) after the application of organic broad‐spectrum sunscreens. The biologic effects of these wavelengths have been demonstrated; however, a dose–response has not been investigated. Ten subjects with Fitzpatrick skin phototype IV‐VI were enrolled. Subjects were irradiated with 2 light sources (80–480 J cm −2 ): one comprising VL with less than 0.5% UVA1 (VL+UVA1) and the other pure VL. Skin responses were evaluated for 2 weeks using clinical and spectroscopic assessments. 4‐mm punch biopsies were obtained from nonirradiated skin and sites irradiated with 480 J cm −2 of VL+UVA1 and pure VL 24 h after irradiation. Clinical and spectroscopic assessments demonstrated a robust response at VL+UVA1 sites compared with pure VL. Histology findings demonstrated a statistically significant increase in the marker of inflammation ( P < 0.05) and proliferation ( P < 0.05) at the irradiated sites compared with nonirradiated control. Threshold doses of VL+UVA1 resulting in biologic responses were calculated. Results indicate that approximately 2 h of sun exposure, which equates to VL+UVA1 dose ( 400 J cm −2 ), is capable of inducing inflammation, immediate erythema and delayed tanning. These findings reinforce the need of photoprotection beyond the UV range. Abstract : Human skin is exposed to visible light (VL; 400–700 nm) and long‐wavelength ultraviolet A1 (UVA1) radiation (370–400 nm) after the application of organic broad‐spectrum sunscreens. The biologic effects of these wavelengths have been demonstrated; however, a dose–response has not been investigated. Threshold doses of VL+UVA1 (370–700 nm) resulting in biologic responses were calculated. Results indicate that approximately 2 h of sun exposure, which equates to an approximate VL+UVA1 dose of 400 J cm −2, is capable of inducing inflammation, immediate erythema and delayed tanning. These findings reinforce the need of photoprotection beyond the UV range.